1980
DOI: 10.5962/bhl.title.119469
|View full text |Cite
|
Sign up to set email alerts
|

Some physiological and biochemical aspects of chilling injury of grapefruit (Citrus paradisi Macf.) with emphasis on growth regulators /

Abstract: Resistance to chilling injury (Cl) of Florida grapefruit has been found to be seasonal, being most resistant in midseason, and a hypothesis that growth regulators (GRs) are involved in resistance to Cl was proposed. The relationship between resistance to Cl and levels of endogenous GRs in the flavedo of 'Marsh' grapefruit was studied to test the hypothesis. A useful, reliable and precise high-performance liquid chromatographic method, coupled with isotope dilution, was developed for routine quantitative analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

1982
1982
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 82 publications
(113 reference statements)
0
9
0
3
Order By: Relevance
“…Grierson (1974) suggested that seasonal changes in either peel pigments or in the plastids containing them could be involved in the resistance of grapefruits to CI. Kawada (1980) could not, however, conÐrm such involvement. It has been suggested that the seasonal variation in the sensitivity of grapefruits to CI is related to the endogenous content of growth regulators at the time of harvest (Kawada 1980).…”
Section: Introductionmentioning
confidence: 84%
“…Grierson (1974) suggested that seasonal changes in either peel pigments or in the plastids containing them could be involved in the resistance of grapefruits to CI. Kawada (1980) could not, however, conÐrm such involvement. It has been suggested that the seasonal variation in the sensitivity of grapefruits to CI is related to the endogenous content of growth regulators at the time of harvest (Kawada 1980).…”
Section: Introductionmentioning
confidence: 84%
“…Hormonal concentrations in fruit, particularly abscisic acid, are high at this time (Yuan et al, 2001). Also during this time, susceptibility of grapefruit to CI and PP is low and fluctuates with the growth stage of the tree (Kawada, 1980). In other words, tree organs compete with one another for growth, as reported in many plant species including citrus (Bustan et al, 1995;Hockema and Etxeberria, 2001;Mengel and Kirkby, 2001).…”
Section: Discussionmentioning
confidence: 90%
“…Estudios llevados a cabo para determinar la implicación de esta hormona en la sensibilidad al frío de los frutos cítricos han dado lugar a resultados contradictorios. Así, en pomelos se observó un paralelismo entre la susceptibilidad al frío y el contenido de ABA en frutos cosechados en distinto estado de maduración y en frutos acondicionados a 29 ºC o con etileno, que presentaron mayores concentraciones de ABA (Kawada, 1980). Por contra, Lafuente et al (1997) observaron en frutos de mandarina 'Fortune', una falta de correlación entre la susceptibilidad a desarrollar esta alteración fisiológica y el contenido en ABA en el momento de la cosecha a lo largo de la campaña.…”
Section: •-unclassified
“…Los miembros de esta familia de proteínas, específica de plantas, se activan durante la formación de nódulos favoreciendo las interacciones simbióticas entre plantas leguminosas y bacterias del género Rhizobium. Estas proteínas poseen dominios conservados ricos en residuos de cisteína con capacidad de unión a diferentes iones divalentes, como el Fe , pudiendo también jugar un papel importante en la fijación del nitrógeno y en la unión a O 2 (Pawlowski et al, 1997;Kawashima et al, 2001;Kato et al, 2002;Gupta et al, 2002). Sheres et al (1990) sugirieron que algunas podrían participar en el transporte transmembrana de metales como el Fe 2+ o Mo 2+ hacia bacteroides para la síntesis de nitrogenasa y posteriormente Pawlowski et al (1997) y Gupta et al (2002) confirmaron esta idea.…”
Section: Estudio Transcriptómico De Los Mecanismos Implicados En La Tunclassified